Flexible Asymmetric Organic-Inorganic Composite Solid-State Electrolyte Based on PI Membrane for Ambient Temperature Solid-State Lithium Metal Batteries - Yang, Ruilu; Zhang, Zheng; Zhang, Qi; Shi, Jian; Kang, Shusen; Fan, Yanchen (Frontiers in Chemistry, 2022)
Solid-state lithium metal batteries have attracted more and more attention in recent years because of their high safety and energy density, with developments in the new energy industry and energy storage industry. However, solid-state electrolytes are usually symmetric and are not compatible with the cathode and anode at once. In this work, a flexible asymmetric organic-inorganic composite solid-state electrolyte consisting of PI membrane, succinonitrile (SN), LiLaZrTaO(LLZTO), Poly (ethylene glycol) (PEO), and LiTFSI were prepared by solution casting successfully. This lightweight solid electrolyte is stable at a high temperature of 150°C and exhibits a wide electrochemical window of more than 6 V. Furthermore, the high ionic conductivity of the flexible solid electrolyte was 7.3 × 10−7 S/cm. The solid-state batteries assembled with this flexible asymmetric organic-inorganic composite solid electrolyte exhibit excellent performance at ambient temperature. The specific discharge capacity of coin cells using asymmetric organic-inorganic composite solid-state electrolytes was 156.56 mAh/g, 147.25 mAh/g, and 66.55 mAh/g at 0.1, 0.2, and 1C at room temperature. After 100 cycles at 0.2C, the reversible discharging capacity was 96.01 mAh/g, and Coulombic efficiency was 98%. Considering the good performance mentioned above, our designed flexible asymmetric organic-inorganic composite solid electrolyte is appropriate for next-generation solid-state batteries with high cycling stability.